Review on biological degradation of biogenic amines in food - Jihao Zeng; Jinhong Wu; Huiyun Chen; Sui Ni (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
In this paper, the application of biological methods to reduce biogenic amine content in foods was introduced. Biogenic amine oxidase, a special protein that can degrade biogenic amine into acetaldehyde, hydrogen peroxide and ammonia, has been introduced in this paper, and two major amine oxidases and their degradation effects on different biogenic amines were briefly reviewed. In addition, various microorganisms that could produce amine oxidase were summarized in this paper, and their application in the fermentation was shown. This short review summarizes the important biological methods currently used to degrade biogenic amines and provides new theoretical guidance for removing or reducing the biogenic amines in foods.